Combination of Ruthenium Complex and Doxorubicin Synergistically Inhibits Cancer Cell Growth by Down-Regulating PI3K/AKT Signaling Pathway - Lin, Ke; Rong, Yi; Chen, Dan; Zhao, Zizhuo; Bo, Huaben; Qiao, Aimin; Hao, Xiaojuan; Wang, Jinquan (Frontiers in Oncology, 2020)
Combinational use of drugs has been a common strategy in cancer treatment because of synergistic advantages in reducing dose and toxicity, minimizing or delaying drug resistance. To improve the efficacy of chemotherapy, various potential combinations have been investigated. Ruthenium complex is considered a potential alternative of the platinum-based drugs due to its significant efficacy and safety. Previously, we reported that ruthenium(II) complex (∆-Ru1) has great anticancer potential and minor toxicity towards normal tissues. However, the therapeutic efficacy and mechanism of action of ruthenium(II) complex combined with other anticancer drugs is still unknown. Here, we investigated the combinational effect of ∆-Ru1 and doxorubicin in different cancer cells. The data assessed by Chou-Talalay method showed significant synergism in MCF-7 cells. Furthermore, the results in antiproliferation efficacy indicated that the combination showed strong cytotoxicity and increasing apoptosis of MCF-7 cells in 2D and 3D multicellular tumor spheroids (MCTSs). Significant inhibition of MCF-7 cells accompanied with increased ROS generation was observed. Furthermore, the expression of PI3K/AKT was dramatically down-regulated, while the expression of PTEN was greatly up-regulated in cells treated with combination of ∆-Ru1 and doxorubicin. The expression of NF-κB and XIAP decreased while the expression of P53 increased and associated with apoptosis. These findings suggest that the combination of ruthenium complex and doxorubicin has a significant synergistic effect by down-regulating the PI3K/AKT signaling pathway in MCF-7 cells. This study may trigger more research in ruthenium complex and combination therapy that will be able to provide opportunities for developing better therapeutics for cancer treatment.